Analysis of Liquidity Ratios and Solvency Ratios at PT Garuda Indonesia (Persero) for the 2019-2024 Period: Analisis Rasio Likuiditas dan Rasio Solvabilitas pada PT Garuda Indonesia (Persero) Periode 2019-2024 - Dameria Naibaho; Yostaria Elfrina Pandiangan; Bernadetta Anita Jerry Simbolon; Friska Sipayung (Jurnal Akuntansi, Keuangan dan Perpajakan, 2026)
This study aims to analyze the liquidity and solvency ratios of PT Garuda Indonesia (Persero) Tbk for the 2019–2024 period and identify internal and external factors influencing the company's inability to meet short-term and long-term obligations. The liquidity ratios studied include the current ratio, quick ratio, and cash ratio, while the solvency ratios include the debt-to-asset ratio, debt-to-equity ratio, and long-term debt-to-equity ratio. The analysis results show a significant decrease in liquidity and increase in debt in 2020–2021 due to an unbalanced funding structure, operational losses, ineffective management, increased interest expenses, and the impact of the COVID-19 pandemic, which reduced revenue. Abstrak Penelitian ini bertujuan menganalisis rasio likuiditas dan solvabilitas PT Garuda Indonesia (Persero) Tbk periode 2019–2024 serta mengidentifikasi faktor internal dan eksternal yang memengaruhi ketidakmampuan perusahaan memenuhi kewajiban jangka pendek maupun panjang. Rasio likuiditas yang diteliti mencakup current ratio, quick ratio, dan cash ratio, sedangkan rasio solvabilitas meliputi debt to asset ratio, debt to equity ratio, dan long term debt to equity ratio. Hasil analisis menunjukkan penurunan likuiditas dan peningkatan utang signifikan pada 2020–2021 akibat struktur pendanaan tidak seimbang, kerugian operasional, manajemen kurang efektif, beban bunga meningkat, serta dampak pandemi COVID-19 yang menurunkan pendapatan.